Binding characteristics of galectin-3 fusion proteins. (27th February 2017) - Böcker, Sophia; Elling, Lothar
Abstract: Galectin-3 modulates cell adhesion and signaling events by specific binding and cross-linking galactoside containing carbohydrate ligands. Proteolytic cleavage by metalloproteinases yields in vivo N-terminally truncated galectin-3 still bearing the carbohydrate recognition domain. Truncated galectin-3 has been demonstrated to act in vivo as a negative inhibitor of galectin-3 due to higher affinity for carbohydrate ligands. We here present our studies on a series of 12 human galectin-3 protein constructs. Truncated galectin-3 (∆1–62 and ∆1–116) and fusions with SNAP-tag and/or yellow fluorescent protein (YFP) display altered binding efficiencies (ratio of maximum binding signal and apparent affinity constant K d ) to asialofetuin (ASF) in solid-phase enzyme-linked immunosorbent assay (ELISA) and surface plasmon resonance (SPR) binding assays. Galectin-3(Δ1–62) and full-length (native) galectin-3 have highest affinity to ASF in ELISA and SPR experiments, respectively, whereas galectin-3(Δ1–116) shows only weak binding. We demonstrate here for the first time that SNAP-tag and YFP fusions of galectin-3 and truncated galectin-3 proteins improve binding efficiencies to ASF. SNAP-tagged galectin-3, galectin-3(Δ1–62) and galectin-3(Δ1–116) are found with significant (3- to 6-fold) higher binding efficiencies in SPR when compared with native galectin-3. Fusion of truncated galectin-3 with YFP renders binding properties similar to native galectin-3, whereas in combination with SNAP-tag improved binding characteristics are obtained. Our results emphasize the importance of the N-terminal domain of human galectin-3 for ligand binding. Most importantly, in combination with fusion proteins suitable for the design of diagnostic and therapeutic tools binding properties can be beneficially tuned. The resulting novel protein tools may be advantageous for potential galectin-3 directed applications in tumor diagnostics and therapy.